Visual detection of human infection with influenza A (H7N9) virus by subtype‐specific reverse transcription loop‐mediated isothermal amplification with hydroxynaphthol blue dye. (30th May 2013) - Nie, K.; Zhao, X.; Ding, X.; Li, X. D.; Zou, S. M.; Guo, J. F.; Wang, D. Y.; Gao, R. B.; Li, X. Y.; Huang, W. J.; Shu, Y. L.; Ma, X. J.
Abstract: A rapid and sensitive H7 and N9 subtype‐specific reverse transcription loop‐mediated isothermal amplification assay was developed respectively for visual detection of human‐infected influenza A (H7N9) virus. The reaction was performed in one step in a single tube at 63°C for 60 min with the addition of hydroxynaphthol blue dye before amplification. The detection limits of both subtype‐specific assays were comparable to those of validated H7 and N9 real‐time PCR assays respectively and no cross‐detection was observed with influenza A pandemic H1N1, H3N2, H5N1, H9N2 or influenza B virus. The assays were evaluated further with H7N9 virus‐infected clinical specimens.